The Role of Islamic Religious Education Teachers in Enhancing Student Discipline - Marzuki Marzuki; Cica Filya (Jurnal Wawasan Sarjana, 2024)
The aim of this study is to understand the interaction patterns between Islamic Religious Education (IRE) teachers and students as part of the process of improving student discipline at SMAN 5 Kendari. This research employs a qualitative approach. Data collection techniques include observation, interviews, and documentation. The informants in this study consist of the vice principal of curriculum, the coordinator of guidance and counseling teachers, teachers, and students. Data analysis is conducted using the Miles and Huberman model, which includes data collection, data reduction, and drawing conclusions. Based on the results of the study, it can be concluded that the interaction patterns used by IRE teachers to improve student discipline at SMAN 5 Kendari involve both two-way and multi-directional interaction patterns. Two-way interactions occur both inside and outside the classroom, such as question-and-answer sessions during lessons. IRE teachers also tend to take a soft, personal approach in interacting with students and consistently instill moral messages, ethical values, and relate religious teachings to present and future life, thereby broadening students' religious understanding. Additionally, two-way interaction outside the classroom is reflected in the practice of the “5 S” (greeting, addressing, smiling, politeness, and courtesy) when students meet their teachers.